Profiling students' algebraic thinking ability in solving problems System Of Linear Equations Two Variables in vocational educational schools - Eryanti, Ika; Sallah, Emmanuel Kwadzo; Gakuba, Emmanuel (International Journal of Progressive Mathematics Education, 2022)
Based on the results of data analysis and discussion of research results, it was concluded that students with high algebraic thinking ability category were able to fulfill all indicators of algebraic thinking on problem solving problems. For students with moderate algebraic thinking ability categories, students have not been able to think analytically and dynamically and organize, in other words, they have not been able to fulfill all indicators of algebraic thinking on problem solving problems. Meanwhile, for students with low thinking ability category, students have not been able to think analytically and dynamically and organizationally, as evidenced by students who have difficulty in the elimination method step, namely students are not able to complete the stages of the elimination method of one of the variables x or y correctly. So, the values ​​of x and y obtained by students are wrong. In addition to these errors, students also did not write down what value conclusions were intended/looked for in the problem, in other words, they had not been able to fulfill all the indicators of algebraic thinking in problem solving questions.